Effects of single and co-immobilization on the product specificity of type I pullulanase from Anoxybacillus sp. SK3-4 - Kahar, U.M.; Chan, Kok Gan; Sani, M.H.; Mohd Noh, N.I.; Goh, K.M. (Elsevier, 2017)
Type I pullulanase from Anoxybacillus sp. SK3-4 (PulASK) is an unusual debranching enzyme that specifically hydrolyzes starch α-1,6 linkages at long branches producing oligosaccharides (≥G8), but is nonreactive against short branches; thus, incapable of producing reducing sugars (G1–G7). We report on the effects of both single and co-immobilization of PulASK on product specificity. PulASK was purified and immobilized through covalent attachment to three epoxides (ReliZyme EP403/M, Immobead IB-150P, and Immobead IB-150A) and an amino-epoxide (ReliZyme HFA403/M) activated supports. Following immobilization, all PulASK derivatives were active on both short and long branches in starch producing reducing sugars (predominantly maltotriose) and oligosaccharides (≥G8), respectively, a feature that is absent in the free enzyme. This study also demonstrated that co-immobilization of PulASK and α-amylase from Anoxybacillus sp. SK3-4 (TASKA) on ReliZyme HFA403/M significantly changed the product specificity compared to the free enzymes alone or individually immobilized enzymes. In conclusion, individual or co-immobilization caused changes in the product specificity, presumably due to changes in the enzyme binding pocket caused by the influence of carrier surface properties (hydrophobic or hydrophilic) and the lengths of the spacer arms.